The bubble close-off density of ice in Antarctic ice sheets - Higashi, Akira; Nakawo, Masayoshi; Enomoto, Hiroyuki (1983)
P(論文) Measuring methods of the density and the total gas content in ice cores were developed considering various sources of systematic errors. The special attention was forwarded to the method of correction for the effect of surface-exposed air bubbles. True density ρ_t and the total gas content R were obtained for ice cores drilled at three sites (S 48,H 231 and Z 102.5) of different altitudes in the Soya drainage basin and the Shirase drainage basin, East Antarctica. The bubble close-off densities ρ_c calculated from obtained data with an appropriate assumption of particle paths exhibit their increasing tendency with increasing elevation of the sites of close-off. The relationship between the reduced void ratio a_c and the temperature T_c, both at the close-off, exhibits a little higher level with almost the same gradient than the result obtained by RAYNAUD and LEBEL (Nature, 281,289,1979). departmental bulletin paper